A portable myoelectric-robotic system to prevent muscle stiffness and numbness - Sidek, Shahrul Na'im; Haja Mohideen, Ahmad Jazlan; Wan Sulaiman, Wan Nizam Hakim (2010)
Electromyography is a clinical measurement of electrical activities from muscle tissue. In this work, we develop a myoelectric-robotic system to acquire human electromyogram (EMG) signal which is portable to be used in preventing muscle stiffness and numbness. The problem of muscle stiffness and numbness occurs due to long period of muscle passivity. This is a major problem faced by individuals who are elderly, bedridden or wheelchair bound during their recuperation periods. The proposed system can monitor and record muscle activity of the individual noninvasively, and activate a robotic system to perform a series of pre-specified tasks. We anticipate the human-robot synergism could engage the affected individuals more effectively by providing some 'excitement' in activating their muscles to avoid stiffness and numbness.